Design and validation of DNA probe sets for a comprehensive interphase cytogenetic analysis of acute myeloid leukemia - Döhner, Konstanze; Scholl, Claudia; Sallath, Jörg; Fröhling, Stefan; Schlenk, Richard Friedrich; Bentz, Martin; Stilgenbauer, Stephan; Lichter, Peter; Döhner, Hartmut (Blood, 1996)
The objective of this study was to design DNA probe sets that enable the detection of chromosome aberrations in acute myeloid leukemia (AMU by interphase cytogenetics using fluorescence in situ hybridization (FISH) and to compare the results of interphase cytogenetics with those of conventional chromosome banding analysis. One hundred five consecutive patients with adult AML entered on a multicenter treatment trial were studied with a comprehensive set of DNA probes recognizing the most relevant AML-associated structural and numerical chromosome aberrations: translocations t(8;21), t(15; 17), and t(11q23); inversion inv(16); chromosomal deletions (5q-, 7q-, 9q-, 12p-, 13q-, 17p-, and 20q-); and chromosomal aneuploidies. Interphase cytogenetics was particularly sensitive for detecting the AML-specific gene fusions: 3 additional cases of inv(16) and 1 additional case of t(8;21) were identified by FISH that were missed by banding analysis, whereas equal numbers of t(11q23) and t(15;17) were detected. Five additional cases of trisomy 8q, 3 more cases of trisomy 11 q, and 2 more cases of trisomies 21q and 22q were shown by FISH. These aberrations were either masked in complex karyotypes or identified in cases in which conventional banding analysis failed. On the other hand, the DNA probes selected were not informative to detect 1 case of 5q-, 9q-, and 20q-. In 5 cases, clonal aberrations were detected on banding analysis for which no FISH probes were selected. In conclusion, interphase cytogenetics proved to be more sensitive for detecting AML-specific chimeric gene fusions and some partial trisomies. Interphase cytogenetics provides a powerful technique complementary and, with further development of diagnostic DNA probes, even an alternative to chromosome banding studies for the cytogenetic analysis of AML.
Elektronische Reproduktion der Druck-Ausgabe 21. Dezember 2020
Gesehen am 31.10.2024